The Role of Motivation, Discipline, and Work Environment in Improving Members' Performance - Sugeng Sugiharto; Boge Triatmano; Sina Setyadi (Trescode Green Organization, 2024)
This study aims to analyze the impact of motivation, work discipline, and work environment on the performance of Pusdik Hanudnas Surabaya members. The study was carried out at the Surabaya Hanudnas Education Center, with a total of 70 respondents comprising non-commissioned officers and officers. This is census research. The analytical method uses several linear regression analysis techniques to determine the impact of the dependent variable (X) on the independent variable (Y). The study shows that motivation, work discipline, and work environment significantly influence the performance of employees at Surabaya Hanudnas Education Center. Motivation, work discipline, and a responsive work environment positively affect member performance by ensuring timely completion of tasks, with the work environment being the most significant factor and having the most impact on member performance. Quality, quantity, motivation, discipline, and the work environment all significantly influence the success of Pusdik Hanudnas Surabaya members. The research aims to provide valuable insights for practitioners and the Surabaya Hanudnas Education Center regarding how members' attitudes towards motivation variables, work discipline, and work environment impact performance. It can also serve as a reference for implementing strategic measures to enhance the performance of Hanudnas Pusdik members in Surabaya.